User Satisfaction Analysis of Academic Information System Using End-User Computing Satisfaction (EUCS) - Nurdin, Ali; Lubis, Muharman (Yayasan Asmin Intelektual Berkah, 2024)
Galuh University Academic Information System (SIAKAD) is an information system that supports the academic activities of students, lecturers and employees within Galuh University. As a system that is in direct contact with its users. It is essential to focus on quality of the system utilised by users on a regular basis since the interaction between the system and humans is ideal when both parties give stimuli and reactions (actions & reactions) that support each other, if only If it takes place in one direction, the interaction will experience obstacles or even goal bias. The research was conducted to identify user satisfaction levels who use the system. The elements that determine user satisfaction with academic information systems were examined using the End-User Computing Satisfaction (EUCS) model approach. Data was gathered by observation, interviews, literature research, and questionnaires distributed to Galuh University academic information system users. Based on the existing theoretical basis, statistical analysis was carried out through statistical tests, Specifically, simple linear regression tests were conducted using the SPSS application. The research results showed that the five variables had a significant positive influence on user satisfaction of academic information systems, but the ease of use variable had a significant contribution. the highest was 59.4% for user satisfaction In comparison to other variables like content, accuracy, format, and timeliness, although overall the influence of these variables was still at a moderate level of influence. The research results also recommend updates to the information system to increase user satisfaction.